IMPLEMENTASI ILMU FIQIH MATERI WUDHU DAN SHALAT DENGAN KREASI METODE BELAJAR YANG MENYENANGKAN - soim (JURNAL ILMIAH INNOVATIVE (Jurnal Pemikiran Dan Penelitian), 2024)
This research is based on various obstacles found in the world of teaching, especially in Madrasahs. Madrasas as religious-based schools try to balance knowledge with knowledge about religion. Education on the correct procedures for ablution and prayer must be taught as early as possible, that's the reality. On the basis of these things this research was conducted, by utilizing various sources of literature, the researcher collected data, reviewed the data, filtered the data, and reprocessed the data into new data. So that from these efforts the results obtained include; 1) Development of educator creativity to maximize the teaching process. 2) Fun teaching methods encourage students' interest and desire to learn. 3) As an obstacle to the lack of availability of media as tools and materials as well as infrastructure to implement fun learning activities, so that the established method cannot be carried out optimally. Keywwords: fiqh, study method, media